An Efficient and Reusable Multifunctional Composite Magnetic Nanocatalyst for Knoevenagel Condensation - Yao, Nan; Tan, Jin; Liu, Yang; Hu, Yu Lin (Synlett, 2019)
A range of multifunctional magnetic metal–organic framework nanomaterials consisting of various mass ratios of the metal–organic framework MIL-53(Fe) and magnetic SiO2@NiFe2O4 nanoparticles were designed, prepared, characterized, and evaluated as heterogeneous catalysts for the Knoevenagel condensation. The as-fabricated nanomaterials, especially the nanocatalyst MIL-53(Fe)@SiO2@NiFe2O4(1.0), showed good catalytic performance in the Knoevenagel condensation at room temperature as a result of synergistic interaction between the Lewis acid iron sites of MIL-53(Fe) and the active sites of the magnetic SiO2@NiFe2O4 nanoparticles. In addition, the heterogeneous catalyst was readily recovered and a recycling test showed that it could be reused for five times without significant loss of its catalytic activity, making it economical and environmentally friendly.
Keywords: metal-organic frameworks; magnetic nanocatalyst; Knoevenagel condensation; cooperative catalysis; heterogeneous catalysis; iron catalysis